2022
DOI: 10.1038/s41598-022-19841-x
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional associations between physical activity and sleep in older adults: a multilevel analysis using polysomnography

Abstract: Although recent studies have examined the bidirectional associations between physical activity and sleep parameters, few have focused on older adults utilizing objective assessments, such as polysomnography. This micro-longitudinal observational study included 92 Japanese older adults (aged 65–86 years) who underwent objective evaluations of sleep quality using polysomnography and completed subjective sleep-related questionnaires. Activity levels were assessed using an accelerometer. Polysomnography, subjectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
22
1
Order By: Relevance
“…Although the sensitivity of N1 and N3 in determining sleep stage was low, the agreement was generally high; hence, there is a possibility of home measurements in the future with a portable EEG device. Third, drawing on our earlier studies [14,15], patients with OSA exhibited reduced N2 sleep and increased N1 sleep (there might have been a misinterpretation of N1 and N2) (Figs. 1a and 1b), even when their AHI was not greater than 100 [26].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although the sensitivity of N1 and N3 in determining sleep stage was low, the agreement was generally high; hence, there is a possibility of home measurements in the future with a portable EEG device. Third, drawing on our earlier studies [14,15], patients with OSA exhibited reduced N2 sleep and increased N1 sleep (there might have been a misinterpretation of N1 and N2) (Figs. 1a and 1b), even when their AHI was not greater than 100 [26].…”
Section: Discussionmentioning
confidence: 87%
“…1 and Table 2). In this study, apnea was categorized using the AHI as mild (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) in 20 patients (25.9%), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in 17 patients (22.1%), and severe (> 30) in 34 patients (44.1%). Six patients (7.9%) were suspected of having apnea during screening; however, they had an AHI of < 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study cannot establish night-to-night temporal dynamics in the onset of the observed diet-dependent changes. Most participants were habitually quite physically active, and their training status may potentially have masked some diet-dependent effects on sleep [33]. Larger studies are warranted to explore potential interindividual mediation by, for example, weight status, dietary and physical activity habits, genetics, and potential interactions with gut microbiome-induced signaling [25,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, low correlations between objective and subjective assessments of sleep quality have been reported [ 39 , 40 ]. In addition, skilled personnel are needed to install polysomnography electrodes, though it should be noted that polysomnographic recording of sleep at home has become possible [ 41 ]. Although beneficial effects of time-restricted eating on sleep were not reported, no adverse effects on sleep were found.…”
Section: Effects Of Time-restricted Eating On Sleep and Its Mechanism...mentioning
confidence: 99%